Sexual Violation toward Children - Murdiyanto, Murdiyanto (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The research done to know the factors that caused sexual violation toward children and its prevention effort. The researc took place in North Celebes Province, under the consideration the province ranks ninth in sexual violence towards children. Data gathered through interview, observation, documentary analysis, and analysed by qualitative descriptive technique. The result found that the causal factors of sexual violation towards children were a lack of interaction between parent and children, the punishment toward the perpetrator was weak, the development of technology which easily accessed by children, and promiscuity among youth. The pepretators of sexual violation toward children shoul be punished maximum, plus additional punishment for not repeating it. The development of technology should be controlled by closing the sites on violation and pornography. Having reference to related institutions both government and privat which have commitment to the victims, giving guidance and service reference, so the victims find the way out of their problem. It needs involvement all parts, not just the goverment but all existing elements. All institutions of victims services needed to be proactive to follow out the cases without receiving report. Phisical violation belongs to health institution to cure, for trauma needs involment several institutions as emphaty attitude for the victims. The Ministry of Social Affairs, through General Directorate of Social Rehabilitation, through Directory of Children Affairs, hoped can create a program to minimize sexual violation towards children.